Healing Hearts and Fostering Connections: Mitigating Behavioral Challenges in the Classroom Through Educator Training on Trauma-Transformational Practices - Ford, Veronica L.; Haigh, Kimberly; Hernandez, Gina (International Journal of Learning and Development, 2024)
Trauma and toxic stress are known to have devastating effects on child development and the number of children reporting Adverse Childhood Experiences (ACEs) is continuously on the rise. Exposure to trauma has been proven detrimental to children’s mental and physical health, socio-emotional wellbeing, behavior, and academic performance leading to decreased school engagement, and increased high school dropout rates. Additionally, the negative effects of trauma and adversity on students’ abilities to process and retain information are sometimes outwardly manifested in the learning environment making classroom management and teaching challenging for educators. Educators have a unique opportunity to intervene and provide support to negate the effects of childhood trauma and ACEs by utilizing trauma-informed practices with their students. This paper explores how engaging education professionals in training on the implementation of trauma-transformational practices - through Child Wellness Institute’s Healing Hearts Series: Trauma 101 Workshop - promotes their ability to build healthy connections with their students that foster healing while learning and improves educational outcomes.